Shareholders’ Dividend Preference in The Nigerian Capital Market - Salawudeen, Aishat; Isa, Muhammad Aminu; Dandago, Kabiru Isa (UUM Press, 2022)
Aside from the fact that no legislation requires, as we believe, that management has a distinct fiduciary commitment to shareholders, no act prioritizes the shareholder. The management’s fiduciary duty is solely to the corporation. Investors, on the other hand, have a votive claim to the corporation’s residual value once all other obligations have been met. The aim of this survey was to empirically investigate the dividend preference of shareholders in the Nigerian capital market with specific reference to listed manufacturing firms in Nigeria. The study used the design of an investigation using questionnaires and interviews. The target population was 500 shareholders selected based on stratified random sampling out of 682,100 shareholders that is 0.07 percent of the total population. The snowball sampling technique was used to recruit potential respondents from among the shareholders’ acquaintances. The study used a final sample size of 300 respondents from the shareholders. The validity and reliability of the instrument were tested using factor analysis and a Cronbach’s alpha coefficient of 0.72 was obtained. The mean ranking showed that shareholders do have significant dividend preferences which favor cash dividends and support a bird in the hand is worth two in the bush explanation. Given that in practice, shareholders prefer companies with stable and predictable dividend payments, this study could be used to correct and predict the direction of a company’s dividend payments and that the stability of dividend payments change over time.